Knowledge and Understanding Influence the Values and Attitudes toward Artificial Intelligence (AI) of Accounting Professionals - สุขจำลอง, พรทิพย์; เลิศภิรมย์สุข, สุขมงคล; สุขะวิริยะ, เรืองโรจน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to study the Knowledge and understanding influence the values and attitudes toward artificial intelligence (AI) of accounting professionals. The sample group consisted of 400 accounting professionals working in business establishments within the Bangkok metropolitan area. A questionnaire was used as the primary data collection tool. Statistical analyses included frequency, percentage, mean, and standard deviation. Hypothesis testing was conducted using the t-test and One-way ANOVA.The hypothesis testing results indicated that accounting professionals in Bangkok with different gender, age, education level, work experience, monthly income, and expertise had differing values and attitudes toward AI. Furthermore, the findings revealed that the overall values and attitudes of accounting professionals toward AI were at a very high level. The most positively perceived aspect of AI was its ability to reduce errors and eliminate unnecessary work processes.